2011
DOI: 10.1002/bies.201100035
|View full text |Cite
|
Sign up to set email alerts
|

Into the deep: New discoveries at the base of the green plant phylogeny

Abstract: Recent data have provided evidence for an unrecognised ancient lineage of green plants that persists in marine deep-water environments. The green plants are a major group of photosynthetic eukaryotes that have played a prominent role in the global ecosystem for millions of years. A schism early in their evolution gave rise to two major lineages, one of which diversified in the world's oceans and gave rise to a large diversity of marine and freshwater green algae (Chlorophyta) while the other gave rise to a div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
89
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(94 citation statements)
references
References 93 publications
(214 reference statements)
3
89
0
2
Order By: Relevance
“…From an evolutionary point of view, of advantage to the green plants evolving to terrestrial environments might have been avoidance of the stress of OA, which is known to have occurred at the end of the Ordovician period (Veron, 2008). Green plants have been suggested to have evolved about 400 million years ago (Leliaert et al, 2011), when atmospheric CO 2 was as high as 3,000 mL L 21 and the extinction of marine organisms occurred with an ancient OA event (Berner, 2006;Veron, 2008).…”
Section: Possible Mechanisms and Implicationsmentioning
confidence: 99%
“…From an evolutionary point of view, of advantage to the green plants evolving to terrestrial environments might have been avoidance of the stress of OA, which is known to have occurred at the end of the Ordovician period (Veron, 2008). Green plants have been suggested to have evolved about 400 million years ago (Leliaert et al, 2011), when atmospheric CO 2 was as high as 3,000 mL L 21 and the extinction of marine organisms occurred with an ancient OA event (Berner, 2006;Veron, 2008).…”
Section: Possible Mechanisms and Implicationsmentioning
confidence: 99%
“…This group arose after an endosymbiotic event between a cyanobacterium-related organism and a heterotrophic eukaryote that was at the origin of the Plantae, also named Archaeplastida, a supergroup of eukaryotes that also includes the red algae and glaucophytes (Leliaert et al, 2011). The extant Streptophyta include the land plants as well as diverse freshwater algal lineages, while the Chlorophyta include some freshwater algae and all marine representatives (Chapter II).…”
Section: A General Considerationsmentioning
confidence: 99%
“…The Chlorophyta and Streptophyta possess the following common unique features: a double membrane bound plastid containing chlorophyll b as the main accessory pigment and starch, as well as a unique stellate structure linking pairs of microtubules in the flagellar base. The Chlorophyta form a strongly supported group in molecular phylogenies and are characterized by unique biochemical and ultrastructural features (Leliaert et al, 2011).…”
Section: A General Considerationsmentioning
confidence: 99%
“…Analyses of molecular data, in some cases supported by ultra-structural information, have shown that the unicellular planktonic Prasinophyceae form a paraphyletic group of about ten lineages, only some of which have been formally described as classes (Marin and Melkonian, 2010;Leliaert et al, 2011). Ancestors of the extant prasinophytes gave rise to the morphologically and ecologically diverse core Chlorophyta, which include three major classes: Ulvophyceae, Trebouxiophyceae and Chlorophyceae (UTC).…”
Section: Introductionmentioning
confidence: 99%